Analyzing the Ratio Decidendi: Court of Appeals Decision Reversing District Court’s Ruling in an Election Process Dispute - Angga Eka Setiawan; Temesgen Abebe Degu (Mimbar Keadilan, 2024)
In practice, the General Election process disputes must be brought before the State Administrative Court. Decision Number 757/Pdt.G/2023/PN Jkt.Pst exceeded its jurisdictional limits. This is because the Central Jakarta District Court ruled over the dispute when it did not have the authority. The decision was revoked by decision Number 230/Pdt/2023/PT DKI due to its violation of applicable regulations regarding absolute competence. The legal basis for this revocation has been underscored in Article 470 of Law Number 7 of 2017 concerning General Elections and Article 25 of Law Number 48 of 2009 concerning Judicial Power. This study aims to determine the legal principle of decision Number 230/Pdt/2023/PT DKI, which overturned the Central Jakarta District Court's decision regarding the dispute over the General Election process. The research methodology utilized in this inquiry is normative legal research incorporating a statutory, conceptual, and case-based approach. The legal materials utilized include primary legal materials, such as laws, regulations, and court decisions, and secondary legal materials, including legal books, research journals, and theses pertinent to the research area. The findings indicate that the verdict issued by the DKI Jakarta High Court Judges' Panel was justified. As part of the Supreme Court's voorpost function, the Court of Appeals is responsible for addressing judicial technical and administrative matters that arise at the initial level.